Impact of exchange rate on trade flow in nigeria - Victor Ushahemba Ijirshar; Isa J. Okpe; Jerome T. Andohol (CBN Journal of Applied Statistics, 2022)
This study examines the impact of exchange rate on trade flow in Nigeria from 1986 to 2021. The study utilises linear and nonlinear autoregressive distributed lag (ARDL and NARDL) models to test the J-Curve hypothesis and the Marshall-Lerner condition in Nigeria. The study found symmetric effects of exchange rate on trade balance, exports, and imports. The findings also show that real exchange rate depreciation has a strong negative influence on trade balance and exports in the short run but positive in the long run, exhibiting the shape typology of the J-curve. Furthermore, the study reveals evidence of the Marshall-Lerner condition since the sum of the elasticities of export and import is greater than unity. Thus, there is room for long run net trade improvement. The study suggests the need for the Nigerian government to grant investment incentives to domestic firms to expand production and improve on the quality of output to reduce import.
Keywords: D51; F14; O24; 330; Exchange rate; exports; imports; J-curve; real effective exchange rate; trade balance